2020
DOI: 10.1021/acssensors.0c00784
|View full text |Cite
|
Sign up to set email alerts
|

Branched Au Nanoparticles on Nanofibers for Surface-Enhanced Raman Scattering Sensing of Intracellular pH and Extracellular pH Gradients

Abstract: The development of plasmonic-active nanosensors for surface-enhanced Raman scattering (SERS) sensing is important for gaining knowledge on intracellular and extracellular chemical processes, hypoxia detection, and label-free detection of neurotransmitters and metabolites, among other applications in cell biology. The fabrication of SERS nanosensors for optophysiology measurements using substrates such as nanofibers with a uniform distribution of plasmonic nanoparticles (NPs) remains a critical hurdle. We repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 69 publications
1
72
0
Order By: Relevance
“…( b ) Branched AuNPs on PS-P4VP nanofiber: uniform distribution of well-dispersed branched AuNP arrays, which allow for significantly higher SERS response than spherical AuNPs, and schematic representation of the fabrication procedure with application in the direct measure of the internal pH of cells and external pH gradients in cell culture environments. Adapted with permission from [ 107 ] Copyright (2020) American Chemical Society.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…( b ) Branched AuNPs on PS-P4VP nanofiber: uniform distribution of well-dispersed branched AuNP arrays, which allow for significantly higher SERS response than spherical AuNPs, and schematic representation of the fabrication procedure with application in the direct measure of the internal pH of cells and external pH gradients in cell culture environments. Adapted with permission from [ 107 ] Copyright (2020) American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…P-ATP was selected as a target analyte to demonstrate the high SERS sensitivity and reproducibility of the substrate, which showed an EF of about 9.0 × 10 3 and a LOD of 10 −14 mol/L (Figure 4a). Recently, Zhao et al [107], combined the low-invasiveness and high spatial resolution of nanofibers and branched AuNPs (nanostars and nanoribbons) arranged in a monolayered distribution into a reproducible SERS biosensor. The authors reported the spatial mapping of the pH gradient in a cellular environment with applications in cancer diagnosis and non-invasive cell monitoring.…”
Section: Polymeric Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the three kinds of mainstream pH probe molecules, 4-mercaptobenzoic acid was often widely used as pH Raman report molecules by various research groups to construct pH SERS probes [35,36]. The main reasons why it can be used as a Raman report molecule for the construction of pH Raman probe are its simple structure, wide pH response range, high photochemical stability, mercaptan mediated metal surface affinity and its ability to form a single molecular layer on the metal surface through molecular self-assembly.…”
Section: -Mercaptobenzoic Acid (4-mba)mentioning
confidence: 99%
“…The colloidal approach has been applied to image the pH in living cells [ 13 ]. The literature has been summarized in reviews [ 10 , 14 ], while more recent work has been achieved on gold colloids to increase the number of hot spots in hyperbranched Au [ 15 ]. On the other hand, the plasmonic nanostructures have also been obtained from nanofabrication as an array of nanoneedles [ 16 ] on a polymeric substrate, which demonstrated pH sensing on a mechanically stable array.…”
Section: Introductionmentioning
confidence: 99%